Reduction of redundant neural network activation during the performance of a task: a functional model applied to problem-solving strategies - Gupta, S.K. (Medical hypotheses, 1999)
Problem-solving is explained by various paradigms. For example, epistemological paradigms state that, when the task is novel, and pursued of one's free will, problem-solving occurs in discontinuous, discernable phases. It is then also a microdevelopmental process, i.e. involves the construction of knowledge through qualitatively different stages of thought. Quantitative methods are used to focus on the redundancy of function as well as the concept of selective activation of the brains's neural network during the performance of a task. In this model, the following are identified: (a) performance circuits: (i) NP, no performance; (ii) LP, low performance; (iii) MP, medium performance; (iv) HP, high performance; and (v) VHR, very high performance; (b) task performance groups: (I) NOU, no outline used; (serves as a control); (ii) OU, outline used; (iii) MOU, modified outline used; (iv) QMOU, qualitatively and quantitatively modified outline used. An example of a distribution that one obtains is (for the efficiency of activation of the HP): QMOU:MOU:OU. NOU is in the ratio of : 400:100:50:5 (out of 103trials). The subject is hence educated as to the mechanism of various strategies that he may use in everyday problemsolving.